Identifikasi Kebersihan dan Kesehatan SDN Tanah Kali Kedinding V/579 - Oji Pranata Sihombing; Muhammad Arno; Moch Hikmal Safiyuddin; Fadlan Herdianto Abdi; Anib Muslim Mailulloh Salim; Muhammad Nur Rahmatullah; M Dimas Prayoga (Nusa Cendana University, 2025)
This study aims to identify the environmental hygiene and health conditions at SDN Tanah Kali Kedinding V/579B Surabaya, as well as to determine the clean and healthy living behavior (PHBS) of the school community and the physical health status of students. The method used is descriptive qualitative with a survey and observation approach. Data collection techniques include direct observation of sanitation facilities and waste management, semi-structured interviews with teachers and students, and height and weight measurements of 30 fifth-grade students. The results of the study indicate that the general condition of the school environment is good, with well-maintained toilets, the availability of soapy handwashing facilities, and regular waste management. Awareness of the school community in implementing PHBS is quite high, but the interview results indicate the need for ongoing hygiene education. The UKS program has been running but still requires strengthening socialization and involvement of the entire school community. The results of anthropometric measurements show variations in student nutritional status, with some students being underweight or overweight. The conclusion of this study is that the condition of hygiene and health at SDN Tanah Kali Kedinding V/579B is already considered good, but it is necessary to improve the ongoing education program and routinely monitor students' physical health to support the creation of a healthy and comfortable school environment.